Symposium 1: Perspectives on identity within networked learning: Symposium Introduction - Davis, Jane (Proceedings of the International Conference on Networked Learning, 2014)
Identity has long been referenced, within research into networked learning communities, as the image of the student, self-constructed and presented as product of ongoing participation in the learning community and engagement with its histories, behaviours and artefacts. Such research has often been reliant on the dialogic analysis of engagement within a formal bounded learning space. Papers presented in this symposium suggest that the closely bounded, two-dimensional nature of such portrayal requires further consideration. This symposium presents three different perspectives which range from an exploration of dimensions of identity and their impact on the networked learning experience, consideration of the nature of identity as networked learning communities extend beyond the formal learning place and embrace the potential opportunities of open online spaces, and an exploration of digital identity through social curation. Participants will be invited to consider the positions presented within the papers and will then be encouraged to participate in post-presentation discussion and a mapping activity that encourages reflexive consideration of issues of identity as they impact on their own learning and/or that of students with whom they engage within networked learning communities.